General characteristics of legal norms - Umaña Luna, Eduardo (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This treatise brings together fundamental notions of Law built throughout a lifetime of professional practice and academicstudy by its author, Dr. Eduardo Umaña Luna (RIP). This posthumous publication becomes not only a necessary tribute forthose who with their example and virtue defended the principles of law in legal practice, but also an essential object of studyfor current generations, since not only its fundamental concepts are still valid, but also that the changes in the legal structuresof the country allow with this study to make a historical comparison between the current reality and that of that time. Thearticle studies the meanings and applications of law, justice and jurisprudence, as well as legality and illegality, natural law,historicism and positive law and the various schools formed around these postulates.